A Comparison Performance Analysis of QoS WLANs: Approaches with Enhanced Features. (12th November 2007) - Papapanagiotou, Ioannis; Paschos, Georgios S.; Devetsikiotis, Michael
Abstract : The main contribution of this work is to compare and enhance known methods for performance analysis of the IEEE 802.11e MAC layer, such as the use of Markov chains, queuing theory, and probabilistic analysis. It is the first paper that bases its outputs upon comparison of metrics such as complexity, flexibility, and accuracy, leading to the novel use of a metamodeling comparison. For the analysis, complexity theory and theL -square distance method for accuracy are used. In addition, the proposed analyses carry by themselves scientific interest, because they are extended enhancements with the latest EDCA parameters. A form of the PMF of the MAC delay and first-order moments are found using the PGF complex frequency domain function. The analyses incorporate a Gaussian erroneous channel in order to reflect the real conditions of the MAC layer.